Superficial CD34-positive fibroblastic tumor and PRDM10-rearranged soft tissue tumor are overlapping entities: a comprehensive study of 20 cases - Perret, Raul; Michal, Michael; Carr, Richard A; Velasco, Valérie; Švajdler, Marian; Karanian, Marie; Meurgey, Alexandra; Paindavoine, Sandrine; Soubeyran, Isabelle; Coindre, Jean-Michel; Boidot, Romain; Charon-Barra, Céline; et al. (Histopathology, 2021)
AIMS: Superficial CD34-positive fibroblastic tumor (SCD34FT) and PRDM10-rearranged soft tissue tumor (PRDM10-STT) are rare mesenchymal tumors. These lesions have clinicopathological similarities, but their relationship remains controversial. This study aimed to characterise a series of cases of SCD34FT and PRDM10-STT. METHODS AND RESULTS: Ten lesions each of SCD34FT and PRDM10-STT were studied using immunohistochemistry, array-comparative genomic hybridisation (aCGH), RNA sequencing and exome sequencing. Tumors mainly occurred in young adults, were generally small (< 5 cm) and arose predominantly in the superficial soft tissues of the lower extremities. Follow-up data were available in 15 cases (SCD34FT, n = 7, median 16 months; PRDM10-STT, n = 8, median 14 months), local recurrences occurred in four cases (SCD34FT, two of 10; PRDM10-STT, two of 10), while no distant spread was documented. Morphologically, tumors were relatively well-circumscribed and composed of sheets and fascicles of spindle and pleomorphic cells showing low mitotic activity (< 1/mm²) without necrosis. Other findings included: granular cell change, lipoblast-like cells, ectatic blood vessels with fibrinous material, myxoid stromal changes, metaplastic bone and increased mitotic activity (> 1/mm²). All tumors diffusely expressed CD34, while pan-keratin and desmin were commonly seen focally. SynCAM3 was diffusely expressed in 12 cases (SCD34FT, n = 5; PRDM10-STT, n = 7), independently of fusion status. aCGH profiles were 'flat' (PRDM10-STT, n = 4; SCD34FT, n = 2) and exome sequencing showed no recurrent pathogenic mutations (PRDM10-STT, n = 2; SCD34FT, n = 4). Overall, the only morphological features seen exclusively in PRDM10-STT were myxoid stromal changes (three of 10) and metaplastic bone (two of 10). CONCLUSION: We expand the current knowledge on PRDM10-STT and SCD34FT and provide additional evidence for considering them as overlapping entities.
Keywords: DNA-Binding Proteins; genová přestavba; RNA sequencing; comparative genomic hybridisation; mladiství; imunohistochemie; Middle Aged; mužské pohlaví; Antigens, CD34; Adult; nádory měkkých tkání; mladý dospělý; Transcription Factors; superficial CD34-positive fibroblastic tumor; Gene Rearrangement; Biomarkers, Tumor; transkripční faktory; Immunohistochemistry; Young Adult; ženské pohlaví; nádorové biomarkery; Humans; Fibroblasts; lidé středního věku; PRDM10; sarcoma; Soft Tissue Neoplasms; DNA vazebné proteiny; dospělí; antigeny CD34; Female; Adolescent; lidé; Male; fibroblasty